Digital Images: Interaction and Production - Matthews, Linda; Perin, Gavin (International journal of creative interfaces and computer graphics, 2011)
The valence of any visual paradigm and its accompanying technologies is subject to the contingencies of political regimes and cultural shifts. The instigation, implementation and even reconfiguring of any associated technological system effects a translation and adjustment to the structure and use of these supporting mechanisms that both re-defines the relationship between object and viewer and ultimately influences its translation into material form. The permeation of digital systems throughout contemporary urban space is typified by Internet Protocol webcam systems, instigated by civic authorities for surveillance and the imagistic promotion of iconic city form. This paper examines how this system’s reception and subsequent translation of transmitted data signals into digital information not only presents new material to mediate people’s engagement with public space, but moreover, how it presents new opportunities for the designer to materialize its three-dimensional form within the spatial ambiguity of virtual and real-time environments.